Evaluation of Yield and Competition Indices in Sweet Corn (Zea mays saccharata L.)-Soybean (Glycine max) Intercropping System - Canggih Nailil Maghfiroh; Datik Lestari; Retno Sari Mahanani; Sumarlina; Tia Sofiani Napitupulu (Akta Agrosia, 2026)
Intercropping is a cultivation strategy that can enhance land use efficiency and crop productivity compared to monoculture. This study aimed to evaluate the advantages of sweet corn–soybean intercropping systems over monoculture through crop competition analysis. The experiment was conducted at the Innovation Farm of Politeknik Negeri Jember using two treatments, namely monoculture and intercropping, each with three replications. Observed parameters included sweet corn yield components (number of cobs, cob weight, diameter, and length) as well as the calculation of Land Equivalent Ratio (LER), Area Time Equivalent Ratio (ATER), aggressivity, Competitive Ratio (CR), and Actual Yield Loss (AYL). Sweet corn yield data were analyzed using a t-test to determine significant differences between treatments. The results showed that intercropping provided higher efficiency with LER of 1.32 and ATER of 1.25, indicating an increase in land efficiency by 32.3% and time efficiency by 24.6% compared to monoculture. Sweet corn was the dominant crop with aggressivity of 1.42, CR of 3.31, and positive AYL of 1.03, while soybean was suppressed with aggressivity of –1.42, CR of 0.30, and negative AYL of –0.39. The t-test indicated no significant differences in sweet corn yield between monoculture and intercropping (p > 0.05). Thus, the sweet corn–soybean intercropping system is proven to be more efficient and has the potential to be adopted as a sustainable cultivation strategy under limited land conditions.